Multicultural Mentorship Education: A Critical Tool for National Unity and Integration in Nigeria - Salako, Ekima Tina (Advances in Social Sciences Research Journal, 2016)
The learner population is constantly changing, so, educators deal with learners from a wide cross-section of cultural backgrounds. Consequently, there is need to focus on help-seeking behaviors and help-providing behaviors of mentors based on race, social class and ethnicity. There is always the concern that most schools may not be adjusting rapidly enough to the fact that learners from different cultures may need an alternative style of teaching and learning in order to realize their optimal potential in the global 21st century classroom. In realizing this view of social and cultural differences in the behavior of the minority students, as a matter of need, an appropriate education of citizens through multicultural mentorship education is being advocated. As traditionally defined, mentoring is a one-to-one relationship between an experienced and a less experience person over a period of time. Mentors empower students' success by being role models and guide as a result of challenges which come from a variety of sources. Therefore, this paper investigated multicultural mentorship education as a critical tool for national unity and integration. One research question was raised and a null hypothesis was generated and tested at 0.05 level of significance. The study adopted a quasi experimental design. Participants were one hundred and fifty junior secondary III students purposively selected from three secondary schools in Ogun State, South-West region of Nigeria. Data were analyzed using descriptive statistics of frequency count, percentage, mean and standard deviation. Inferential statistics of Pearson product moment correlation was used to test the hypothesis. The findings of this study revealed that effective refocusing of traditional or conventional teaching method with a view of complimenting it with multicultural mentorship educational strategy would enhance service delivery plus national unity and integration.